Lymphocytic gastritis and celiac disease - Viscido, Angelo; Latella, Giovanni (Polish Journal of Pathology, 2021)
We read with great interest the review article “Lymphocytic gastritis” by Puderecki et al., which was recently published in your journal [1]. The article describes the features of lymphocytic gastritis (LG), a rare form of gastritis with unclear pathogenesis. The diagnosis of LG is based on histology which reveals intraepithelial lymphocytosis (> 25 intraepithelial lymphocytes per 100 gastric surface and foveolar epithelial cells). The endoscopic appearance of LG can vary from normal mucosa to aphthous erosions, nodularity, local spots, polyps, and ulcers. The most common locations of the lesions are the body and the antrum. With regard to etiology, Celiac disease (CD) is the main reported cause of LG, followed by Helicobacter pylori infection. After a careful review of the argument, Puderecki et al. conclude that there is no one exact cause of LG, and rather than being a separate disease, LG is more likely a sign of the disease with which it is associated [1]. We wrote to remark on the strong connection between LG and CD. Such a connection may allow some etiopathogenetic and clinical speculations.